Android Geographic Information System with AHP for Strategic MSME Location Selection - Ami Amanda; Triase Triase (Bigint Computing Journal, 2026)
Strategic site selection for micro, small, and medium enterprises (MSMEs) requires transparent assessment of spatial and operational criteria. This study develops an Android geographic information system integrating the Analytic Hierarchy Process (AHP) and OpenStreetMap to screen 30 locations across 25 sub-districts in Asahan Regency, Indonesia. Five criteria were defined from literature, field observation, and consultation with one local-government practitioner. Accessibility received the highest weight (0.3333), followed by safety and comfort (0.2667), proximity to crowds (0.2000), infrastructure (0.1333), and local resources (0.0667). Sekitar Stasiun Kisaran ranked first (0.0391), only 0.0004 above the next two alternatives. The system links numerical priorities with interactive mapping and provides an auditable mobile workflow for preliminary location screening. However, CR = 0.000 results from deterministic ratio construction, not broad expert consensus, and the ranking should not be interpreted as a causal prediction of business performance.